Improving teachers' competencies in differentiated learning through a lesson study-based learning community at SMPN 1 Tulakan - Gembong, Sardulo; Yuhanna, Wachidatul Linda; Yunianto, Taufik Hidayat Eka (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
SMPN 1 Tulakan is one of the Sekolah Penggerak in Pacitan Regency. This school requires the assistance of a learning community and the implementation of differentiated learning. The activities carried out as a solution to the problems of SMPN 1 Tulakan are training and mentoring for differentiated learning through lesson study-based learning communities. This training was carried out for 3 months June-August 2024. The participants were 32 teacher in SMPN 1 Tulakan. The approach used is participatory by involving teachers directly in theory and practice. The result of this activity was the teacher's achievement in understanding the learning community material, 83% really understood and 17% said they understood. Teachers' achievement in understanding differentiated learning material was 90% very understanding and 10% understanding. The results of the questionnaire on achieving understanding of the concept of lesson study showed that 87% of teachers really understood and 13% of teachers understood. In general, as many as 90% of teachers are able to apply the concept of differentiated learning and lesson study in class according to their role as model teachers or as observers. The conclusion of this community service program is that teachers understand material related to learning communities, differentiated learning and lesson study. Teachers are able to implement lesson study to activate the learning community of SMPN 1 Tulakan. Teachers increase their competence in practicing differentiated learning through lesson study at SMPN 1 Tulakan.